2013
DOI: 10.1021/ac401445a
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based Microfluidic Electrochemical Immunodevice Integrated with Nanobioprobes onto Graphene Film for Ultrasensitive Multiplexed Detection of Cancer Biomarkers

Abstract: To the best of our knowledge, this was the first report on the integration of a signal amplification strategy into a microfluidic paper-based electrochemical immunodevice for the multiplexed measurement of cancer biomarkers. Signal amplification was achieved through the use of graphene to modify the immunodevice surface to accelerate the electron transfer and the use of silica nanoparticles as a tracing tag to label the signal antibodies. Accurate, rapid, simple, and inexpensive point-of-care electrochemical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(123 citation statements)
references
References 37 publications
2
119
0
2
Order By: Relevance
“…Wu et al [45] first reported on the integration of a signal amplification strategy in a microfluidic paper-based electrochemical immunodevice for the multiplexed detection of cancer biomarkers (AFP, CEA, CA 125 and CA 153). In this approach, eight working electrodes, sharing one pair of counter and reference electrodes, were modified with GR/chitosan and coated with AFP, CEA, CA 125 and CA 153 capture antibodies.…”
Section: No Label-free Innovative Electrochemical Immunosensorsmentioning
confidence: 99%
“…Wu et al [45] first reported on the integration of a signal amplification strategy in a microfluidic paper-based electrochemical immunodevice for the multiplexed detection of cancer biomarkers (AFP, CEA, CA 125 and CA 153). In this approach, eight working electrodes, sharing one pair of counter and reference electrodes, were modified with GR/chitosan and coated with AFP, CEA, CA 125 and CA 153 capture antibodies.…”
Section: No Label-free Innovative Electrochemical Immunosensorsmentioning
confidence: 99%
“…[26] Integrating the signal amplification methods on paper electrochemical microfluidic chip enables researches to use the excellent electrical conductivity properties of graphene and the large specific surface area of silica nanoparticles for improving the sensitivity of such assay (Figure 4c). [45] Four kinds of cancer biomarkers: alpha-fetoprotein (AFP), CEA, cancer antigen 125 (CA125), and carbohydrate antigen 153 (CA153) are quantitatively analyzed simultaneously using this devices, which shows good stability, reproducibility, and accuracy with an LOD less than 10 pg. A rather straightforward and highly practical system can sensitively screen cystic fibrosis for newborns by electrodepositing copper nanoparticles on gold electrode for the improvement of signal and introducing magnetic nanoparticles as support for immune reaction.…”
Section: Papermentioning
confidence: 99%
“…For instance, researchers have integrated multi-walled carbon nanotubes (MWCNTs) into μPADs to covalently immobilize probe antibodies and enhance the signal output of electrochemical immunoassays by utilizing MWCNT's high surface-to-volume ratio and superior electrical conductivity 4 . Graphene and gold nanorods have also been utilized on μPADs for electrochemical 8 and optical biosensing 9 , respectively. Nevertheless, the preparation of these nanomaterials could be complex and costly, which may hinder the wide use of μPADs.…”
Section: Introductionmentioning
confidence: 99%